ESTABLISHMENT AND COMPARISON OF NEPHROTOXICITY ASSOCIATED WITH THE USE OF VARIOUS DOSES OF CONLISTIN IN RABBITS: Nephrotoxicity With Colistin in Rabbits - Bader, Zarafshan; Waheed, Akbar; Hashim, Rizwan (Pakistan Armed Forces Medical Journal, 2016)
Objective: This study was designed to assess the nephrotoxicity associated with various doses of Colistin sulfate in rabbits. Study Design: Laboratory based randomized controlled trials, Place and Duration of Study: This study was held at Army Medical College, Rawalpindi. Study period was from 15th April till 30th April 2012. Material and Methods: Rabbits were divided into three groups of six rabbits each. Baseline serum urea, serum creatinine and serum electrolytes were estimated. A loading dose of colistin infusion was given followed by I.M injections for six days. Rabbits were sacrificed 24 hours after the last dose and both kidneys were sent for histopathology. Results: There was marked nephrotoxicity in high toxic group where as in low toxic group mild nephrotoxicity was evident. Conclusion: It was established that we may safely escalate dose of colistin up to four times the currently recommended schedule to combat the threat of resistance when using it for one to two weeks.